2012
DOI: 10.1155/2012/928123
|View full text |Cite|
|
Sign up to set email alerts
|

Sterile Endophthalmitis after Intravitreal Injections

Abstract: Sterile endophthalmitis appears as an infrequent complication of intravitreal injections and seems to develop mainly in the context of the off-label use of drugs that have not been conceived for intravitreous administration. The aetiology of sterile endophthalmitis, independently of the administered drug, remains uncertain and a multifactorial origin cannot be discarded. Sterile inflammation secondary both to intravitreal triamcinolone acetonide and to intravitreal bevacizumab share many characteristics such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 52 publications
0
44
1
1
Order By: Relevance
“…66 However, repeated intraocular injection significantly increases the risk of ocular complications, including discomfort or pain, subconjunctival or vitreal hemorrhage, acute and sterile intraocular inflammation, uveitis, and endophthalmitis. 66,67 Reviews of clinical trials and patient charts to determine the safety of AMD intravitreal therapies have found that incidence rates for endophthalmitis range from 0 to 0.16%. [68][69][70][71][72][73] A longitudinal study by Rasmussen et al 29 showed that of 600 eyes that began AMD intravitreal treatment, a third of the eyes still were receiving treatment after 4 years with no change in visual activity.…”
Section: Discussionmentioning
confidence: 99%
“…66 However, repeated intraocular injection significantly increases the risk of ocular complications, including discomfort or pain, subconjunctival or vitreal hemorrhage, acute and sterile intraocular inflammation, uveitis, and endophthalmitis. 66,67 Reviews of clinical trials and patient charts to determine the safety of AMD intravitreal therapies have found that incidence rates for endophthalmitis range from 0 to 0.16%. [68][69][70][71][72][73] A longitudinal study by Rasmussen et al 29 showed that of 600 eyes that began AMD intravitreal treatment, a third of the eyes still were receiving treatment after 4 years with no change in visual activity.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic delay might be explained by the rarity of fungal endophthalmitis and the subacute nature of early infection, or the difficulty of distinguishing true infection from the occasionally observed postprocedural sterile inflammation. 8 The microbiological diagnosis of fungal endophthalmitis is usually based on microscopy and culture of the microorganisms in vitreous fluid. Smears made from these samples may be examined immediately after detecting the fungi by direct microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…As with periorbital injections, intravitreal injections may be repeated for recurrent disease with close monitoring for side effects. In addition to development or progression of cataract and elevation of intraocular pressure, potential adverse effects of intravitreal steroid injections include vitreous hemorrhage, retinal detachment, as well as infectious or sterile endophthalmitis (Marticorena et al 2012). …”
Section: Local Corticosteroidsmentioning
confidence: 99%